User’s Expectations on Interactive Travel Guide eBook: A Case Study - Lee, Angeline; Siti Shukhaila, Shaharuddin; Ng, Giap Weng; Syaryfah Fazidawaty, Wan Busrah (IEEE, 2016)
The use of modern interactive travel guide eBook is becoming a necessity of many destinations to stay competitive and attractive to the modern tourist. The aim of this paper is to study users’ expectations for the development of a mobile travel guide eBook/ book app. Hence, an experimental investigation was conducted to explore and determine users’ demand of acceptance – the requirements and expectations of interactive multimedia features content to bring travel guide eBook to life with video, audio and other interactive features in an engaging way. This study uses primary data analysis from 128 respondents who were randomly chosen in Malaysia and some other countries. A preliminary survey, based on online questionnaires and brainstorming sessions were conducted to identify the influential of users’ perception towards features content requirements and expectations prerequisite. Analyzing reliability and validity factor has been conducted to further support users’ acceptance of travel guide eBook technology revolution. Findings show that there is a significantly high level of potential demand of merging graphic design and interactive multimedia features being implemented in an attractive and meaningful way in the tourism industry.